LATE ROMAN TERRACOTTA LAMPS FROM DRAGONERA (ISTRIA) - Starac, Alka (Rei Cretariae Romanae Fautorum Acta, 2024)
Systematic rescue excavations in the year 2003 at Dragonera on the Western Istrian coast have revealed two Roman villas about 300 metres apart. Both villas were settled from the first to the seventh centuries AD. The better-preserved villa Dragonera–South was built in the Flavian period, and replaced by a new building on the same site at about the year 400. It is worth noting that in same period a nearby Roman villa in Dobrika Bay (Islands of Brijuni) was fortified and progressively turned into a Byzantine castrum of great strategic importance. Most of the lamps, as well as other archaeological finds, belong to the late Roman villa of Dragonera-South. In it were found 36 late Roman lamps, while in the nearby villa Dragonera-North only eight were discovered.